2011
DOI: 10.1152/ajpheart.00199.2010
|View full text |Cite
|
Sign up to set email alerts
|

A high-fructose diet worsens eccentric left ventricular hypertrophy in experimental volume overload

Abstract: Bouchard-Thomassin (LVH) can be affected by diet manipulation. Concentric LVH resulting from pressure overload can be worsened by feeding rats with a high-fructose diet. Eccentric LVH is a different type of hypertrophy and is associated with volume overload (VO) diseases. The impact of an abnormal diet on the development of eccentric LVH and on ventricular function in chronic VO is unknown. This study therefore examined the effects of a fructose-rich diet on LV eccentric hypertrophy, ventricular function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
(43 reference statements)
2
28
0
Order By: Relevance
“…The present study, however, supports the deleterious effect of long term high fructose feeding on ischemic-reperfusion injury, caused by impaired normal endothelial function, induction of oxidative stress and systemic inflammation [27,48,63,64]. The results obtained in the present study thus imply an important role of NOS in high fructose diet induced IRS [14,48] and also in atorvastatin mediated protection against ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 67%
“…The present study, however, supports the deleterious effect of long term high fructose feeding on ischemic-reperfusion injury, caused by impaired normal endothelial function, induction of oxidative stress and systemic inflammation [27,48,63,64]. The results obtained in the present study thus imply an important role of NOS in high fructose diet induced IRS [14,48] and also in atorvastatin mediated protection against ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 67%
“…Although interstitial fibrosis is not an early feature of this animal model of eccentric LV remodeling, significant accumulation of collagen is present in later stages (≥6 months). 16,22 Our results suggest that the dilated hearts of Cpt-treated AR animals tolerated the abnormal hemodynamic overload and maintained a near normal myocardial metabolic profile. We previously showed that blood pressure in AR animals treated with Cpt is only slightly reduced and had similar findings in this protocol.…”
Section: Discussionmentioning
confidence: 65%
“…Enzymatic activities for hydroxyacyl-Coenzyme A dehydrogenase, hexokinase, and citrate synthase were determined as previously described. 16 Enzymatic activities for carnitine palmitoyl transferase and malonyl-CoA decarboxylase enzymatic activity determination were also previously described elsewhere.…”
Section: Enzymatic Activity Determinationsmentioning
confidence: 99%
“…Enzymatic activities for hydroxyacyl-Coenzyme A dehydrogenase (HADH), phosphofructokinase (PFK) and citrate synthase (CS) were determined as previously described [7].…”
Section: Enzyme Activity Determinationsmentioning
confidence: 99%
“…Metformin is an AMPK activator widely used for the management of type 2 diabetes but its potential to help maintain normal myocardial metabolism and/or prevent LVH is not well understood [6]. We have previously demonstrated that LV volume overload caused by aortic valve regurgitation causes severe eccentric LVH and also significantly impairs myocardial metabolism [7].…”
Section: Introductionmentioning
confidence: 99%